The Chemical Science of Javanese Herbal Medicine (Jamu Jawa) as a Tourism Potential in Karangrejek, Wonosari, Yogyakarta - Tristanti; Sujarwo; Fitta Ummaya Santi; Yudan Hermawan (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this research is to describe the elements of Javanese, Medicine. Jamu has been a part of Indonesian life for hundreds of years, especially in Java. Javanese Jamu is an herbal drink made from various local medicinal plants, such as turmeric, temulawak, ginger, kencur, and many more. This concoction is believed to have health benefits, ranging from maintaining immunity to helping cure various minor ailments.  The study method used is descriptive qualitative method and tends to use analysis. The theoretical basis is used as a basic reference in preparing the study report to match the conditions in the field. In addition, the theoretical basis can also provide an overview of the background of the study as material for discussion. The ability to collect data is an important factor in determining the validation of the study conducted. Data collection in this case is obtained secondarily, namely through documents or literature studies. The results of the study found that jamu as a tourist attraction has shown various benefits and potential that can support cultural and health tourism in Indonesia. With its background as a traditional medicinal plant-based drink that has been used by Javanese people for centuries, jamu not only provides health benefits but also has cultural and economic appeal.